Functional and Behavioral Responses of the Natural Enemy Anthocoris nemoralis to Cacopsylla pyri, at Different Temperatures - Laura A. Reeves; Michael P. D. Garratt; Michelle T. Fountain; Deepa Senapathi (Journal of Insect Behavior, 2023)
Anthocoris nemoralis is the dominant predator of pear sucker ( Cacopsylla pyri ) in the UK. Anthocoris nemoralis migrates into orchards in spring or is introduced as a biocontrol agent, reaching peak population levels in July-August, contributing to effective control of summer pear sucker populations. However, due to temperature dependent development and metabolism there are concerns that C. pyri populations or feeding rates may increase due to changing climatic conditions. Thus, how A. nemoralis responds to temperature, impacts its ability as a biocontrol agent. Functional response assays, monitoring attack rate and handling time of A. nemoralis and behavioral assays, using Ethovision tracking software occurred, to assess the impact of temperature on predation. Experiments were conducted at current and future July-August mean temperatures, predicted using RCP4.5 and RCP8.5 (medium and high, representative concentration pathway) emissions scenarios, using 2018 UK Climate Projections (UKCP18). All treatments demonstrated a Type II functional response, with female anthocorids demonstrating shorter handling times and higher attack rates than males. Males showed longer prey handling times at 18 °C compared to 23 °C and more time was spent active at lower temperatures for both sexes. Females did not show significant differences in attack rate or handling time in response to temperature. Overall prey consumption was also not significantly affected by temperature for either sex. This study suggests that anthocorids are likely to remain effective natural enemies under future predicted temperatures, due to non-significant differences in prey consumption.